Conformational Analysis and Photochemistry of 2-Chloro-6-fluorobenzoic Acid Monomers in Solid Xenon - Fausto, Rui; ILDIZ, GÜLCE ÖĞRÜÇ (My University, 2019)
In this study, the conformational space of 2-chloro-6-fluorobenzoic acid (CFBA) has been investigated theoretically using density functional theory, with the B3LYP functional and the 6-311++G(d,p) basis set, and experimentally by matrix isolation infrared spectroscopy. The calculations allowed identification of 3 different non-planar conformers of the compound, the lowest energy form (I) exhibiting the carboxylic acid group in the cis arrangement (O=C- O-H dihedral equal to ~0°), and the two higher energy forms (II and III) bearing a trans carboxylic group (O=C-O-H dihedral equal to ~180°) (see Figure). The energies of conformers II and III are larger than that of the most stable conformer I by 17.07 and 17.31 kJ mol-1 , respectively. The considerably large energy difference between the two trans conformers and the cis form implies that only this last species should exist significantly populated in the room temperature gas phase conformational equilibrium. In consonance with the theoretical predictions, only conformer I could be trapped from the room temperature vapor of the compound into low temperature (10 K) solid xenon. The theoretical vibrational characterization of all 3 conformers of CFBA and the assignment of the experimental IR spectrum of conformer I were undertaken.The matrix-isolated monomers of the compound were then irradiated z/7 situ using narrowband UV light with L = 235 nm. The major observed reaction channel was decarboxylation, leading to production of CO2 and l-chloro-3-fluorobenzene. Carbon monoxide was also detected in the infrared spectra of the photolysed solid Xc matrices of the compound, indicated that UV- induced decarbonylation of CFBA takes also place in some extent, though the expected accompanying photoproduct (2-chloro-6-fluorophenol) could not be experimentally sensed.